Cross-modal functional connectivity supports speech understanding in cochlear implant users. (20th August 2022) - Fullerton, Amanda M; Vickers, Deborah A; Luke, Robert; Billing, Addison N; McAlpine, David; Hernandez-Perez, Heivet; Peelle, Jonathan E; Monaghan, Jessica J M; McMahon, Catherine M
Abstract: Sensory deprivation can lead to cross-modal cortical changes, whereby sensory brain regions deprived of input may be recruited to perform atypical function. Enhanced cross-modal responses to visual stimuli observed in auditory cortex of postlingually deaf cochlear implant (CI) users are hypothesized to reflect increased activation of cortical language regions, but it is unclear if this cross-modal activity is "adaptive" or "mal-adaptive" for speech understanding. To determine if increased activation of language regions is correlated with better speech understanding in CI users, we assessed task-related activation and functional connectivity of auditory and visual cortices to auditory and visual speech and non-speech stimuli in CI users ( n = 14) and normal-hearing listeners ( n = 17) and used functional near-infrared spectroscopy to measure hemodynamic responses. We used visually presented speech and non-speech to investigate neural processes related to linguistic content and observed that CI users show beneficial cross-modal effects. Specifically, an increase in connectivity between the left auditory and visual cortices—presumed primary sites of cortical language processing—was positively correlated with CI users' abilities to understand speech in background noise. Cross-modal activity in auditory cortex of postlingually deaf CI users may reflect adaptive activity of a distributed, multimodal speech network, recruited to enhance speech understanding.